Interação farmacocinética do tacrolimo: a influência de prednisona, ácido micofenólico ou sirolimo - Park, Sung In [UNIFESP] (2010)
Background & objective: This study was conducted to evaluate timedependent pharmacokinetic changes and drug interactions over the first 6 months after transplantation in kidney transplant recipients receiving tacrolimus, prednisone, and mycophenolate mofetil or sirolimus. Patients & Methods: Pharmacokinetic assessments were done at day 7 and months 1, 3, and 6 in kidney transplant recipients receiving tacrolimus plus prednisone with either mycophenolate mofetil (2 g/day, n=13) or sirolimus (15 mg loading dose, 5 mg for 7 days followed by 2 mg/day, n=12). Results & Discussion: There were no differences in main demographic characteristics or in mean prednisone doses during the first six months after transplant. From day 7 to month 6 there was a 65% increase in tacrolimus dose corrected exposure (dose corrected area under the curve) in patients receiving mycophenolate mofetil cotherapy (p= 0.005) and a 59% increase in tacrolimus dose corrected exposure in patients receiving sirolimus cotherapy (p=0.008). From day 7 to month 6 there was a 72% increase in mycophenolate dose corrected exposure (p=0.001) and a 65% increase in sirolimus dose corrected exposure (p=0.008). Tacrolimus dose corrected exposure was 23% lower in patients receiving sirolimus compared to mycophenolate mofetil (p=0.012) on average over the study period. Prednisone dose reduction was associated with increase in tacrolimus (in patients receiving sirolimus, p=0.040) and mycophenolic acid (p=0.070) drug exposures. Tercile distribution of tacrolimus drug exposure showed a positive correlation with mean sirolimus exposures (p=0.016). Conversely, tercile distribution of sirolimus drug exposure showed a positive correlation with mean tacrolimus exposures (p=0.004). Conclusions: Time-dependent increases in tacrolimus, mycophenolic acid and sirolimus drug exposures occur up to 6 months after transplantation. Significant drug-to-drug interactions indicate that intense therapeutic drug monitoring is required to avoid under- or over-immunosuppression.